Influências das fusões e aquisições no valor de mercado das instituições bancárias adquirentes - Pessanha, Gabriel Rodrigo Gomes (2014)
Historically, it is possible to observe that mergers and acquisitions (M&A) strategies have resulted in the reformulation of many organizations. Numerous surveys have been conducted in an attempt to understand and explain the reasons why organizations opt for M&A. Given the volume of M & A transactions involving Brazilian companies in the banking industry, this sector was chosen to investigate the impacts of M&A on companies participating in these processes, in an effort to understand the importance of this growth strategy for the results of these financial institutions. The main objective of this study, then, is to verify whether there was value creation (maximization of shareholder wealth) or value destruction (reduction of shareholder wealth) from acquisitions in the short term. We used event-study methodology to evaluate the behavior of stock returns upon the announcement of M&A in Brazilian banking institutions in the period 1994-2009. Results showed that the first day after the announcement of M & A has a positive abnormal, but not statistically significant return. The cumulative return begins to decline after the event occurrence date, but these returns did not show statistical significance. It is concluded that the bank mergers and acquisitions studied did not produce abnormal positive returns for shareholders. These results are consistent with similar studies of the banking industry carried out in other countries.